A Survey On Flower Image Retrieval Based On Saliency Map And Feature Extraction (International Journal of Engineering and Computer Science, 2014)
Content based Image Retrieval is a growing topic under image processing. The main purpose of CBIR System is to help users to retrieve revelent images based on their contents using several feature extraction technique such as color, texture and shape using saliency map. In this paper various extracting methods are discussed, analyzed and compared. To extract the color feature from the image the color moment will be used. To extract texture feature, the image will be in gray-scale and Gabor filter is performed on it. To extract Shape feature Zernike moment and Fourier Descriptor are used.